2019
DOI: 10.1039/c8nj06208k
|View full text |Cite
|
Sign up to set email alerts
|

A novel sensing layer based on metal–organic framework UiO-66 modified with TiO2–graphene oxide: application to rapid, sensitive and simultaneous determination of paraoxon and chlorpyrifos

Abstract: Simultaneous electrochemical detection of paraoxon and chlorpyrifos based on metal–organic framework UiO-66 modified with TiO2–graphene oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(17 citation statements)
references
References 44 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…For example, metal-organic frameworks (MOFs) have received a lot of attention in many different fields, including analytics, so it is not surprising that MOFs were also investigated for pesticide quantification. Karimian et al [ 149 ] applied TiO 2 -functionalized graphene oxide to modify MOF UiO-66 for the simultaneous determination of paraoxon and chlorpyrifos. Appreciable performances were observed, with LODs of 0.2 10 −3 μM (paraoxon) and 1.0 10 −3 μM (chlorpyrifos), and the corresponding linear ranges of 1.0–100.0 10 −3 μM and 5.0–300.0 10 −3 μM, respectively, with the use of square wave voltammetry.…”
Section: Electrochemical Sensor For Water Contaminantsmentioning
confidence: 99%
“…For example, metal-organic frameworks (MOFs) have received a lot of attention in many different fields, including analytics, so it is not surprising that MOFs were also investigated for pesticide quantification. Karimian et al [ 149 ] applied TiO 2 -functionalized graphene oxide to modify MOF UiO-66 for the simultaneous determination of paraoxon and chlorpyrifos. Appreciable performances were observed, with LODs of 0.2 10 −3 μM (paraoxon) and 1.0 10 −3 μM (chlorpyrifos), and the corresponding linear ranges of 1.0–100.0 10 −3 μM and 5.0–300.0 10 −3 μM, respectively, with the use of square wave voltammetry.…”
Section: Electrochemical Sensor For Water Contaminantsmentioning
confidence: 99%
“…Karimian et al demonstrated the Zr-MOF with TiO 2 functionalized graphene oxide@UiO-66 (TGO@UiO-66) for simultaneous detection of paraoxon and chlorpyrifos. The square wave voltammogram (SWV) of TGO@UiO-66/GCE in presence of paraoxon and chlorpyrifos showed two characteristic peaks at 0.45 and 1.3 V. The designed sensor exhibited low detection limits of 0.2 and 1.0 × 10 -9 M within the linear ranges of 1 -100 × 10 -9 M and 5 -300 × 10 -9 M for paraoxon and chlorpyrifos [53]. Bhardwaj et al reported the three-phase composite material consisting of SiO 2 -coated Cu-MOF, single layer graphene, and aniline was synthesized.…”
Section: Mofs With Graphene-based Compositesmentioning
confidence: 99%
“…The sensor showed a low LOD of 0.2 and 1.0 n m for paraoxon and chlorpyrifos, respectively. Furthermore, the prepared sensor was successfully used for pesticide residue monitoring in vegetable samples (Karimian et al., 2019). Guo et al.…”
Section: Recent Studies On Mofs For Pesticide Detection From Food Commentioning
confidence: 99%